Expression of FOXP1 and p53 in Reactive Lymphoid Lesion and B-cell Non-Hodgkin Lymphoma, Large Cell Type - Ita Ellyana1,2,3, Nila Kurniasari4,5,6 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Lymphoproliferative lesions that have morphology between benign and malignant are difficult to diagnoseeven with immunohistochemical and clonality testing. The correct diagnosis is necessary for the prompttreatment. These lesions can also serve as instructive models of lymphomagenesis. FOXP1 plays an importantrole in B-cell development, has a potential oncogene in B-cell Non-Hodgkin lymphoma, and p53 proteinhas a crucial role in the regulation of cell cycle, DNA repair, apoptosis, and senescence tumor suppressionactivity. In this study, we analyze the role of FOXP1 and p53 expression in reactive lymphoid hyperplasiaand B-cell Non-Hodgkin lymphoma, large cell type. 68 paraffin blocks samples from patients diagnosedas reactive lymphoid hyperplasia and B-cell Non-Hodgkin lymphoma, large cell type was sectioned andstained with immunohistochemistry for FOXP1 and p53, and the percentage of nuclear cells showingpositive staining were evaluated. Expression of FOXP1 and p53 in B-cell Non-Hodgkin lymphoma, largecell type is higher than in reactive lymphoid hyperplasia with p=0.001 and cutoff point 45%(CI=95%) forFOXP1 and p=0.001 and cutoff point 7.5%(CI=95%) for p53. There is a significant correlation between theexpression of FOXP1 and p53 in reactive lymphoid hyperplasia and B-cell Non-Hodgkin lymphoma, largecell type (p=0.001). Our findings suggest that high expression of FOXP1 and p53 in B-cell Non-Hodgkinlymphoma may demonstrate the role of FOXP1 and p53 in lymphomagenesis and these markers may helpto distinguish benign and malignant lymphoproliferative lesions.